'Transvenous' pleurocentesis. Issue 5 (September 2020) - Siew, Kelvin Shenq Woei; Hieu, Huynh Quoc; Loch, Alexander
A middle-aged woman had a central venous catheter insertion for fluid resuscitation presented with tachypnea and oxygen desaturation 6 h later. Diagnosis was made based on the chest X-ray performed 6 h after the catheter placement. Thereafter, the patient received appropriate treatment.